Treatment with Antithrombotics in the Last Year of Life—Incidence of Bleeding and Side Effects After Deprescribing - Frisk, Gabriella; Szilcz, Máté; Hedman, Christel; Björkhem-Bergman, Linda (Journal of Palliative Medicine, 2024)
Background: Patients in palliative care are often treated with antithrombotics, even in the late stages of disease. Clear guidelines regarding deprescribing are lacking. Objective: The aims of this study were to investigate bleeding as a side effect of antithrombotic treatments the last year in life and map the timing of deprescribing. Methods: A retrospective cohort study was performed. All medical records were screened for deceased patients admitted to a palliative care unit in Stockholm, Sweden, over a 3-year period. Patients with antithrombotics were identified; data on bleeding, and on side effects due to deprescribing, were extracted from the medical records. Log-binomial models were used to explore factors associated with bleeding. Results: Of 1501 patients, 897 were treated with antithrombotics during the last year of life (mean age 75 years, 41% women). Of these, 56% continued treatment up until the last 3 days of life. Of the 897 patients, 144 (16%) had at least one bleeding during the treatment. The risk for bleeding was significantly higher for men with prostate cancer compared to other cancer forms, adjusted relative risk 1.9 (95% CI 1.1–3.2). No difference in risk for bleeding was found between sex, age groups, type of antithrombotics, or indication. Two patients (0.2%) developed strokes after antithrombotics were deprescribed. Conclusions: Treatment with antithrombotics during the last year of life is associated with a high risk of bleeding. In this cohort, men with prostate cancer seemed to have more side effects of bleeding than other groups. Few experienced side effects from deprescribing.
Keywords: antithrombotics; deprescribing; end of life; palliative care